Effect of Trypan Blue on Descemet Membrane Elasticity. Issue 11 (November 2016) - John, Thomas; Patel, Alpesh; Vasavada, Abhay; Singh, Man; Nath, Vandana; Cheng, Anny M. S.; Sheha, Hosam
Abstract : Purpose: To evaluate the effect of trypan blue on the elastic property of Descemet membrane (DM) by atomic force microscopy. Methods: Human corneas (n = 10) were obtained from the Illinois Eye Bank (Chicago, IL). The DM was isolated and divided into two halves, one half was stained with ophthalmic trypan blue (Vision Blue, 0.06%, DORC International), whereas the unstained other half served as control. The DM samples were then tested using the atomic force microscope. Data were analyzed using the Hertz model for the evaluation of the Young modulus of elasticity. Results: Atomic force microscopy showed higher cantilever deflection on trypan blue–stained DM compared with control, and the difference was statistically significant ( P = 0.03). Force–distance curve analysis also revealed a statistically significant increase in the Young modulus of elasticity in the trypan blue–stained samples (10.5 ± 1.4 kPa) compared with the control (5.8 ± 0.8 kPa), ( P < 0.0001). Conclusions: Our results suggest that trypan blue may decrease DM elasticity and consequently increase its stiffness. This may influence the graft adherence when used for endothelial keratoplasty.